Hemoglobin A1c as screening for gestational diabetes mellitus in Nordic Caucasian women. Issue 1 (December 2016) - Odsæter, Ingrid; Åsberg, Arne; Vanky, Eszter; Mørkved, Siv; Stafne, Signe; Salvesen, Kjell; Carlsen, Sven
Abstract Background Gestational diabetes mellitus (GDM) increases the risk for preeclampsia and macrosomia. GDM is conventionally diagnosed by an oral glucose tolerance test (OGTT). Hemoglobin A1c (HbA1c) is a marker for the average glucose level the last 2–3 months. We aimed to study if HbA1c alone or in combination with patient characteristics can be used to screen for GDM and reduce the number of OGTTs, and whether it could predict preeclampsia or birth weight. Methods 855 women from a previous study on the effect of exercise on GDM prevalence were eligible, whereof 677 were included. GDM was diagnosed by WHO 1999 criteria (GDM-WHO) and modified IADPSG criteria (GDM-IADPSG), at pregnancy weeks 18–22 and 32–36. HbA1c analyzed at pregnancy weeks 18–22 and 32–36, variables from patient history and clinical examination were considered for logistic regression models. The diagnostic accuracy was assessed by ROC curve analysis. Results Accumulated GDM prevalence was 6.7 % by WHO and 7.2 % by modified IADPSG criteria. Nearly a third could potentially have avoided an OGTT by using HbA1c toexclude GDM-IADPSG with a sensitivity of 88 % at week 18–22 and 97 % at week 32–36. Further, 16 % could have avoided an OGTT with a sensitivity of 96 % using HbA1c at week 18–22 toexclude GDM-IADPSG throughout pregnancy. HbA1c was not accurate atdiagnosing GDM-IADPSG, and it was inaccurate at screening for GDM-WHO at any time point. Adding other predictors did not increase the number of potentially avoidable OGTTs significantly. HbA1c was not significantly associated with preeclampsia or birth weight. Conclusions HbA1c could potentially reduce the number of OGTTs.